Micelas de copoli(oxialquileno)s: caracterização, encapsulação e liberação de fármaco - Ribeiro, Maria Elenir Nobre Pinho (2010)
Most drug candidates fail to progress in their formulations due to its low solubility in water. To resolve this issue, block copolymers with surfactant properties have been well investigated. The objective of this study was to investigate the copolymers F87 (E62P39E62), and mixtures thereof E43B14E43 50/50 to 90/10, with increasing proportion of the more hydrophobic copolymer (E43B14E43), the series of diblock EmBn to carry the model drug through different griseofulvin solubilization methods and study their release, and the study of drug solubilization of quercetin and mangiferin E65G5 the copolymers and their applications in order E65G7E65 Entrainment and controlled release of drugs. We used the technique of inversion of the tube for the study of gelling properties of copolymers F87, and mixtures thereof E43B14E43 50/50 to 90/10. To determine the critical micelle concentration (CMC) used the dye solubilization method measured by fluorescence. The solubility of drugs griseofulvin, quercetin and mangiferin in micellar systems was measured by UV-Vis spectrophotometry and systems of copolymers E65G5 E65G7E65 and used the high performance liquid chromatography (HPLC). The pure copolymers and the systems containing the drugs were characterized by infrared spectroscopy (FT-IR), Raman spectroscopy (FT-Raman), X-rays, particle size by dynamic light scattering (Zetasizer), and experiments in vitro release were carried out for some systems. The copolymers F87, E43B14E43, their mixtures, the number of diblock copolymers and EmBn E65G5 E65G7E65 and are promising for administration of hydrophobic drugs, because they showed good solubilising capacity values ​​(Scp). The copolymers were E65G7E65 E65G5 and those who stood out in solubilization of quercetin (HPLC): its micellar system increased the aqueous solubility of quercetin in 253 times at 25 ° C for both copolymers and 124 and 142 times at 37 ° C for the diblock and triblock, respectively, and its particles showed complete encapsulation efficiency of quercetin